2016
DOI: 10.1039/c6ce00795c
|View full text |Cite
|
Sign up to set email alerts
|

Short C–H⋯F interactions involving the 2,5-difluorobenzene group: understanding the role of fluorine in aggregation and complex C–F/C–H disorder in a 2 × 6 isomer grid

Abstract: A 26 isomer grid of six N-(difluorophenyl)benzamides (F 2 -xx) and six N-(phenyl)difluorobenzamides (xx-F 2 ) (xx = 23/24/25/26/34/35) integrating crystal structure analyses (at 294 K), gas phase calculations and conformational analyses is reported. All 12 isomers (C 13 H 9 N 1 O 1 F 2 ) aggregate via N-HO=C intermolecular interactions and usually in combination with intermolecular C-HO/F/ interactions and often FF contacts. The F 2 -25 crystal structure has a remarkably supershort intermolecular C-HF in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(37 citation statements)
references
References 67 publications
1
36
0
Order By: Relevance
“…Nevertheless, a comparison of the ligand geometries in the investigated MOFs reveals that the disorder of the TPE core and one external phenylene ring in 1-F is analogous to that of 1 , which means that the fluorine atoms exert minor intramolecular steric effects on the relative changes of ligand geometry in the case of the noncontracted networks (see Figure S22). Furthermore, looking into the type of intermolecular interactions between subframeworks in 1 and 1-F , the crystal structures show the presence of several weak π···H–C arom and F···H–C arom interactions (characteristic distances from 2.09 to 2.84 Å). …”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, a comparison of the ligand geometries in the investigated MOFs reveals that the disorder of the TPE core and one external phenylene ring in 1-F is analogous to that of 1 , which means that the fluorine atoms exert minor intramolecular steric effects on the relative changes of ligand geometry in the case of the noncontracted networks (see Figure S22). Furthermore, looking into the type of intermolecular interactions between subframeworks in 1 and 1-F , the crystal structures show the presence of several weak π···H–C arom and F···H–C arom interactions (characteristic distances from 2.09 to 2.84 Å). …”
Section: Resultsmentioning
confidence: 99%
“…In related research, we have considered the competition between the F, O=C, N–H, and aromatic rings in terms of influencing interactions and aggregation. 36 We have also speculated on the number of halogen atoms and type of halogen atom needed to tip the interactions from hydrogen bonding toward halogen bonding of the type C–Cl···O=C, C–Cl···N pyridine , and C–Cl···Cl–C. Indeed, research studies on the competition between interactions in crystal structure formation have been pursued with much interest recently in structural systematic studies of extensive series of molecules and in co-crystal formation.…”
Section: Resultsmentioning
confidence: 99%
“… 14 32 Extensive structural studies have been undertaken on series of organohalogens. Examples include the investigation of fluorine in benzamides 33 36 and potential uses of bromine and iodine in agrochemicals. 37 39 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations indicate that the substituent groups do not significantly interfere in the interactions, despite compound 3d (which possesses the ortho -amino group) presenting more H-bonds with the DNA. In addition, we observed the importance of the carbon-hydrogen bond with the fluorine moiety (C-H···F-C) [ 46 , 47 , 48 , 49 ] as an interaction that stabilizes the thioaryl-porphyrins-DNA adduct. The predicted theoretical thermodynamic data (∆G bind ) indicated that all the thioaryl-porphyrin derivatives present spontaneous interaction with DNA fragments ( 3a (−8.8 kcal/mol); 3b (−9.3 kcal/mol); 3c (−9.3 kcal/mol); 3d (−8.8 kcal/mol)).…”
Section: Resultsmentioning
confidence: 99%